Subnational Health Spending and Soft Budget Constraints in OECD Countries - Crivelli, Ernesto (IMF Working Papers; Working Paper ;, 2010)
Government spending on health has grown as a percent of GDP over the last 40 years in industrialized countries. Widespread decentralization of healthcare systems has often accompanied this increase in spending. In this paper, we explore the effect of soft budget constraints on subnational health spending in a sample of OECD countries. We find countries where subnational governments rely primarily on central government financing and enjoy large borrowing autonomy have higher healthcare spending than those with more restrictions on subnational government borrowing.